SEMANTICS OF TRUTH: A CRITICAL ASSESSMENT - Garcia Zarate, Oscar (2008)
This paper assesses Tarski's semantical conception of truth as well as his semanticaldefinition of truth. This done, two arguments in their favour and two against themare articulated. Finally, it is concluded that Tarski's semantical conception of truth hassorne similarities with the deflationary theory of truth, the most relevant of which isthat both theories give considerable importance to sorne versions of the T-scheme.